Production of superfine green tea powder from processing wastes: Characterization of chemical composition and exploration of antimicrobial potential against Ralstonia solanacearum. (May 2019) - Zhang, Hengkai; Chen, Li; Yang, Ting; Liu, Qingyan; Chen, Xiaoxin; Zhang, Yong; Shu, Guowei; Li, Jianke
Abstract: "Green waste" derived from food or agro-industrial has been applied to remove pathogenic bacteria. Green tea waste is polyphenol rich green waste but barely been focused by researchers. We ground the green tea wastes into superfine powder at 4 °C. The median particle size of superfine green tea powder (SGTP) was 9.215 μm. The chemical composition of powder was analyzed by high performance liquid chromatography (HPLC), and was mainly consisting of gallic acid (GA), epigallocatechin gallate (EGCG), caffeine (CAF), and epicatechin gallate (ECG). In vitro experiment indicated that the SGTP significantly inhibited bacterial proliferation of plant pathogen Ralstonia solanacearum GMI1000 in a concentration-dependent manner. However, when the hrpB deletion mutant of GMI1000 was inoculated in medium supplemented with SGTP, the bacterial growth was barely affected. Furthermore, the SGTP significantly decreased the bacterial swimming motility. Scanning electron microscope (SEM) image exhibited that cell damage emerged when bacteria was exposed to medium supplemented with SGTP. Antibacterial activity was compared towards SGTP, tea polyphenol, and tea extract, which suggested that SGTP had potential to be a functional antimicrobial. Our approach of SGTP as antimicrobial would broaden the scope of green waste utilization in a greener, cost-effective, and sustainable approach in future. Highlights: Superfine green tea powder (SGTP) was prepared at 4 °C with D50 9.215 μm. SGTP mainly contained GA, EGCG, CAF and ECG. SGTP hindered bacterial proliferation by cell damage and decreased swimming motility. SGTP exhibited great antimicrobial potential against R. solanacearum .